Association of renal function by measuring glomerular filtration rate with renal dimensions in Pakistan: A Tertiary Care Center Study - Maria Mohiuddin, Mubina Lakhani, Rosheena Nabeel Khan, Uzma Najam, Sarwath Fatimee, Nuzhat Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In kidney morphological changes in size are manifested by renal pathologies and are of great significance in clinical assessment of patients with kidney diseases. Therefore of the objective of this study is to report normative data of renal dimension and its correlation with renal function. Design of the study: It was a cross sectional study Place of study: This study was conducted in a tertiary care hospital, Dr. Ziauddin University Hospital, Karachi from January, 2017 to June, 2017. Material and Methods: Total 250 individuals were included in the study. The participants were recruited through convenient sampling, from Ziauddin University. Study participants were 21 to 60 years of age, who were referred to Radiology department for abdominal contrast CT.All kidney dimensions including kidney length, kidney width and anteroposterior diameter were taken by using 16-slice Multidector computed tomography MDCT scanner. Serum creatinine of study participants was used to calculate eGFR by Modification of Diet in Renal Disease formula. Data was analyzed by using SPSS version 20, Pearson’s correlation was applied to find association between renal measurements and calculated eGFR. Results were reported with confidence level at 95% and P-value ≤ 0.05 was considered to be significant. Results: Renal measurements of study participants were renal length (Right:10.81±0.71, left:11.12±0.73) and renal volume (right: 118.80 ±17.98 cm3, left: 126.00 ±18.36 cm3). Mean glomerular filtration rate was found to be 112.8 ± 11.20 ml/min/1.73 m2. Conclusion: This study concludes that renal length and renal volume are best correlated with glomerular filtration rate by showing a strong significant positive correlation with estimated glomerular filtration rate in study